2021
DOI: 10.4236/health.2021.135040
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Sensitivity to Cold, Menstruation-Related Symptoms and Handgrip Strength in Female University Students in Japan

Abstract: Sensitivity to cold, which is a popular symptom in Japanese women, is associated with various symptoms such as shoulder stiffness and general fatigue. However, an association of sensitivity to cold with muscle strength has not been reported. The aim of the study was to clarify the associations of sensitivity to cold with handgrip strength and with menstruation-related symptoms in female university students in Japan. We recruited 278 female university students in Japan. Sensitivity to cold and menstruation-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Menstruation is a normal physiological phenomenon [ 1 ] that can be influenced by lifestyle [ 2 ], environment [ 3 ], weather [ 4 ] and nutrition [ 5 ]. Studies have shown that perceived experiences of menstruation vary among women and are influenced by the culture of the place where a woman was born [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Menstruation is a normal physiological phenomenon [ 1 ] that can be influenced by lifestyle [ 2 ], environment [ 3 ], weather [ 4 ] and nutrition [ 5 ]. Studies have shown that perceived experiences of menstruation vary among women and are influenced by the culture of the place where a woman was born [ 6 ].…”
Section: Introductionmentioning
confidence: 99%